Common Fixed Point Theorems for Weakly Compatible Mapping by (CLR) Property in Dislocated Metric Spaces - Goyal, A.K.; Gupta, Neelmani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In this paper, we employ the concepts of commutativity, weak compatibility and common limit in the range (CLR) property to derive some common fixed point theorems for six mappings satisfying integral type contractive conditions in complete dislocated metric spaces. Our findings improve and extends some previous results found in the literature. 2010 Mathematical Sciences Classification: 54H25, 47H10